Fabrication and performance of a polyurethane hybrid composite with waste red mud. Issue 6 (12th October 2018) - Yang, Zhengpeng; Shuai, Bo; Zhang, Xuefeng; Yu, Huiling; Zhang, Haibo; Jia, Yuanheng; Zhang, Chunjing; Guan, Xuemao
Abstract : Polyurethane‐based organic–inorganic hybrid composite is attracting increasing attention due to its excellent performance and low cost. Herein, a facile and effective strategy has been proposed for the fabrication of polyurethane/red mud hybrid composite by anchoring red mud particles into a polyurethane frame. The resulting hybrid composite was mainly composed of amorphous polyurethane and crystalline red mud, and its probable formation mechanism was proposed. The polyurethane/red mud composite with micron particles uniformly embedded into the organic phase exhibited satisfactory mechanical performance, and its compressive and flexural strength could come up to 38.6 and 12.4 MPa after complete curing, respectively. Moreover, the hybrid composite displayed impressive thermal stability, flame retardancy, storage stability, and reinforcement performance. The obtained polyurethane/red mud composite shows potential applications in multiple fields (roadway, dam, underground engineering, etc.). POLYM. COMPOS., 40:2424–2431, 2019. © 2018 Society of Plastics Engineers